Simultaneous overexpression of copper- and zinc-containing superoxide dismutase and catalase retards age-related oxidative damage and increases metabolic potential in Drosophila melanogaster. - Sohal, R.S.; Agarwal, A.; Agarwal, S.; Orr, W.C. (Journal of Biological Chemistry, 1995)
The objective of this study was to elucidate the nature of the mechanisms by which overexpression of copper- and zinc-containing superoxide dismutase (Cu,Zn-SOD) and catalase extends life span of Drosophila melanogaster. Experimental flies containing single extra doses of Drosophila Cu,Zn-SOD and catalase genes were compared with appropriate controls at different ages. Overexpression of Cu,Zn-SOD and catalase caused a retardation in the accumulation of 8-hydroxydeoxyguanosine during aging and in response to the exposure of live flies to x-rays. The age-related loss of glucose-6-phosphate dehydrogenase activity (Glu-6-P dehydrogenase) and the increase in the rate of mitochondrial H2O2 generation were less steep in the experimental than control flies. The rate of in vivo oxygen consumption in the latter two-thirds of life span was higher in the experimental than in the control flies. Furthermore, the metabolic potential, or the total amount of oxygen consumed during an average life span, was about 30% greater in the experimental than the control flies. Altogether, results of this study indicate that overexpression of Cu,Zn-SOD and catalase ameliorates the age-related accumulation of molecular oxidative damage and susceptibility to such damage in response to acute oxidative stress while prolonging the metabolic life of flies. The concept that oxidative stress is a causal factor in the aging process is supported.